Analysis of Legal Protection and Children's Health in the Post-Covid 19 Pa℩℩demic (Based on Dignified Justice) - Franciscus Xaverius Wartoyo (Jurnal Smart Hukum (JSH), 2024)
National education is education that is based on Pancasila, the 1945 Co℩℩stituio℩℩ of the Republic of Indonesia, and is rooted in the diversity of Indonesian culture and society, and is responsive to the demands of changing times. The purpose of writing this article is to reveal how the application of education in the post-pa℩℩demic period in the form of prevention and increasing healthy living behavior such as washing hands, wearing masks and so on, accompanied by strict health protocols, is still needed to prevent further transmission. The implementation of legal protection for children's health needs special attention in the post-Covid-19 pa℩℩demic, both in formal and non-formal education. In educational environments, health protocols are still required and students who have a cold or cough are advised to be self-aware and responsible for maintaining health protocols.